Sensorial Behavior of Polypyrrole Nanofibers Prepared by Chemical Oxidative Polymerization - Omar A. Hussein; T. H. Mubarak; Isam M. Ibrahim (Academic Science Journal)
Conductive polymer (CPs) materials include polypyrrole nanofibers (PPy-NFs). The chemical oxidation of pyrrole monomer with Iron (III) chloride in the presence of methyl orange at 3 0C had synthesized polypyrrole nanofibers (PPy-NFs). Polypyrrole nanofibers (PPy-NFs) were determined to be amorphous, based on the XRD spectra. According to the TEM test, PPy is polymerized into one-dimensional nanofibers with a nanofibers structure that has distinct nanofibers diameters with widths varying from (50-100 nm). The PPy-NFs in the manufactured nanostructures were investigated using RAMAN to identify their composition. Additionally, The NH3 gas- sensing performance of the PPy NFs thin films for the prepared molar ratio was tested.